COMPETITIVE ADVANTAGE TOURISM BASED ON E-TOURISM TO IMPROVE TOURIST DESTINATIONS - Ayu Sari (International Journal of Social Science, 2022)
This study aims to determine the influence of the determining component of Competitive Advantage Tourism in increasing tourist destinations based E Tourism. This research was conducted in Kerinci Regency, Jambi Province. The population in this study was (1) Village Government or Local Government (2) Hotel and lodging Managers (3) Restaurant and Restaurant Managers (4) Travel Agency Managers (5) Managers at Attractions (6) Tourism Services Support (7) Local People in tourism destination obtained a total sample of 120 respondents. The data used in this study were primary data through interviews and questionnaires. Data analysis in this study uses a structural equation model with the analysis tool used is to use AMOS. The results of the study obtained a large coefficient of determination of the influence of Competitive Advantage Tourism which can be explained by the variables Built Environment, Operating Sectors, Natural Resources Environment, and Spirit of Hospitality Cultural and E Tourism of 81.4%. While the coefficient of determination of the Tourism Destination equation is 1.004 or the Tourism Destination variable which can be explained by the variability of Tourism Destination and E Tourism is 100%